Analysis of autopsy record of unnatural deaths in Peshawar district - Khalil, Zahid Hussain; Naeem, Mohammad; Adil, Muhammad; Khan, Muhammad Zia-ul-Islam; Abbas, Syed Hussain; ., Faqirullah (Journal of Postgraduate Medical Institute, 2013)
Objective: This study was undertaken to describe the unnatural deaths and their causes in Peshawar andits suburbs. Methodology: This descriptive study was conducted at the Department of Forensic Medicine and Toxicology,Khyber Medical College, Peshawar. Autopsy data from January 2009 to April 2012 was analyzed andonly those cases were selected for the study where the cause of death was unnatural i.e., homicide, suicide,accidental or undetermined. Results: Of a total of 3,265 autopsies due to unnatural causes during 40 months period, 2,839 (87%) weremales and 426 (13%) were females. There were 2,856 cases of homicide – 2,475 (87%) were males and 381(13%) were females, 317 were accidental deaths - 281 (89%) males and 36 females (11%), 66 were suicide cases - 61 (92%) males and 5 females (8%) and 26 were undetermined deaths - 22 males (85%)and 4 (15%) females. Most victims were aged 20-40 years. Most common cause of death was firearm - 2370 cases, blunt trauma 279 cases and bomb blast/explosives 167 cases. Conclusion: The rate of unnatural deaths in Peshawar is very high. Autopsies done during the study periodwere a lot more than previous years. Homicide is the most common manner of death with firearms beingthe most common weapon used. Strict laws should be implemented to limit illegal weapons. Surveillancemust be increased in all parts of the city to reduce the loss of precious human lives.